Technical Evaluation of Bridge Pier Structural Strengthening to Meet Bridge Class Standards Due to Changes in Structural and Traffic Loads - Didik Setyo Purwantoro; Muhammad Nur Fajar; Herlina Arifin; Alfina Maysyurah (JACEE (Journal of Advanced Civil and Environmental Engineering), 2026)
Upgrading bridge specifications from Class B to Class A necessitates a significant increase in structural load capacity. This study evaluates pier P-2, which exhibited capacity discrepancies under new loading standards. The analysis focuses on the stability of existing pile foundations and reinforcement design through modifications to pile-cap dimensions and the addition of piles. The methodology integrates AllPile software with analytical validation via the Chin and Mazurkiewicz methods, alongside axial load tests following ASTM D1143. Structural verification was conducted using the AASHTO LRFD approach to ensure precise load and resistance factors. Static load test results showed a single pile axial capacity of 1,814.23 kN (SF=2). Analysis of the initial 7x3 pile group configuration (21 piles) yielded a total group bearing capacity (Qtg) of 11,995.64 kN. This value is lower than the design axial load (V = 21,228.88 kN), rendering the foundation "unsafe." To achieve stability, reinforcement piles were designed. Utilizing a new static capacity (Qstatic) of 2,875.85 kN (SF=2), the group capacity increased to 12,012.24 kN. With additional reinforcement valued at 16,040.40 kN, the final total capacity (Qtg) reached 28,052.60 kN. This result satisfies safety requirements (Qtg > Vtotal = 23,152.90 kN), confirming the system as "safe." Reinforcement pile depth is set between 38 m to 42 m based on N-SPT values, referencing the calendering results at 34 m.